Relationship between serum matrix Metalloproteinase-9 levels and severity of multibacillary leprosy in patients aged 30 years and under - Fitriyanti; Perkasa, Tengku Arief Buana; Aurora, Wahyu Indah Dewi; Nastiti, Niken Irfa; Ekaputri, Tia Wida; Pratiwi, Rini; Istarini, Attiya (Proceedings Academic Universitas Jambi, 2025)
Background: Leprosy presents a spectrum of immunological responses linked to pathological and clinical manifestations. Matrix Metalloproteinase-9 (MMP-9), an enzyme involved in extracellular matrix degradation and inflammation, has been implicated in cellular immunity. However, the relationship between MMP-9 levels and bacterial load in multibacillary (MB) leprosy remains incompletely understood, particularly across different age groups. Objective: To analyze the relationship between serum MMP-9 levels and Bacterial Index (BI) severity in MB leprosy patients, stratified by age groups. Methods: A cross-sectional comparative study was conducted from October 2017 to September 2018 at Dr. Rivai Abdullah Leprosy Hospital and Sukajadi Community Health Center, South Sumatra, Indonesia. Thirty-two newly diagnosed or recurrent MB leprosy patients were enrolled via consecutive sampling. Serum MMP-9 levels were measured using ELISA, and disease severity was classified by BI (<3 vs ≥3) using Slit Skin Smear. Data were analyzed using unpaired t-tests and Kruskal-Wallis tests, with significance set at P<0.05. Results: Age group and marital status significantly influenced BI severity (P<0.05). Among patients aged <30 years, those with BI≥3 had significantly lower serum MMP-9 levels (2101.44±430.02 ng/L) compared to BI<3 (2621.57±469.37 ng/L; P=0.044). In patients aged ≥30 years, MMP-9 levels were lower in BI≥3 group (1770.19±477.21 ng/L vs 2068.67±550.58 ng/L), but this difference was not statistically significant (P>0.05). Conclusion: Lower serum MMP-9 levels in severe MB leprosy may reflect diminished cell-mediated immunity. The significant inverse relationship between MMP-9 and BI in younger patients suggests age-dependent immunological variations. These findings support MMP-9 as a potential biomarker for disease severity assessment in MB leprosy.